An enantioselective NADP+-dependent alcohol dehydrogenase responsible for cooxidative production of (3S)-5-hydroxy-3-methyl-pentanoic acid. Issue 6 (2nd June 2016) - Takeda, Minoru; Matsumura, Aline Tiemi; Kurosaki, Kaishi; Chhetri, Rajan Thapa; Motomatsu, Shigekazu; Suzuki, Ichiro; Sahabi, Danladi Mahuta
Abstract: A soil bacterium, Mycobacterium sp. B-009, is able to grow on racemic 1, 2-propanediol (PD). The strain was revealed to oxidize 3-methyl-1, 5-pentanediol (MPD) to 5-hydroxy-3-methyl-pentanoic acid (HMPA) during growth on PD. MPD was converted into an almost equimolar amount of the S -form of HMPA ( S -HMPA) at 72%ee, suggesting the presence of an enantioselective MPD dehydrogenase (MPD-DH). As expected, an NADP + -dependent alcohol dehydrogenase, which catalyzes the initial step of MPD oxidation, was detected and purified from the cell-free extract. This enzyme was suggested to be a homodimeric medium-chain alcohol dehydrogenase/reductase (MDR). The catalytic and kinetic parameters indicated that MPD is the most suitable substrate for the enzyme. The enzyme was encoded by a 1047-bp gene ( mpd1 ) and several mycobacterial strains were found to have putative MDR genes similar to mpd1 . In a phylogenetic tree, MPD-DH formed an independent clade together with the putative MDR of Mycobacterium neoaurum, which produces opportunistic infections. Graphical abstract: : Cooxidation of 3-metyl-1, 5-pentanediol to (3 S )-5-hydroxy-3-methyl-pentanoic acid by strain B-009.